Normal adrenocorticotropic hormone levels do not exclude adrenal insufficiency during immune checkpoint inhibitor therapy: evidence from clinical, steroid, and structural analyses - Ishibashi, Yuria; Baba, Ryuta; Okada, Akira; Otagaki, Yu; Kodama, Takaya; Egusa, Gentaro; Nagano, Gaku; Matsuda, Tsuguka; Miura, Ryoichi; Ono, Atsushi; Tsuge, Masataka; Hattori, Noboru; et al. (Frontiers in Endocrinology, 2025)
IntroductionImmune checkpoint inhibitor-induced isolated adrenocorticotropic hormone (ACTH) deficiency (ICI-IAD) represents a critical endocrine immune-related adverse event (irAE) that may become life-threatening without timely diagnosis. Most cases present with suppressed ACTH and cortisol levels; however, a subset of patients shows preserved ACTH levels despite biochemical evidence of adrenal insufficiency. The mechanism and clinical implications underlying this discordance remain poorly defined. This study aimed to investigate the pathophysiological basis and clinical significance of preserved ACTH in patients with ICI-IAD.MethodsThis study involved retrospective and prospective analysis of 49 patients diagnosed with ICI-IAD. Based on plasma ACTH levels, patients were categorized into ACTH-preserved (≥10 pg/mL) and ACTH-depleted (<10 pg/mL) groups. Comparisons included clinical characteristics, hormone responses to stimulation tests, steroid metabolite levels, and molecular features of circulating ACTH.ResultsThe ACTH-preserved phenotype accounted for 14% of the cohort. Clinical characteristics—including cancer types and ICI regimens—did not differ significantly between the two groups. Despite preserved ACTH levels, cortisol and downstream steroid production remained equally suppressed. All patients who underwent the Synacthen test showed impaired adrenal reserve, confirming that adrenal insufficiency occurred even in cases with preserved-range ACTH values. Corticotropin-releasing hormone stimulation tests revealed similarly blunted pituitary responses in both groups. Gel filtration chromatography identified high-molecular-weight ACTH forms in the preserved group, suggesting altered proopiomelanocortin processing or post-translational modifications that impaired ACTH bioactivity.ConclusionsAdrenal insufficiency may occur when plasma ACTH levels remain within or above the normal range. Diagnosis based solely on ACTH measurements risks underrecognition of ICI-IAD. Comprehensive endocrine assessment—including dynamic hormone testing and detailed steroid profiling—enhances diagnostic accuracy and informs timely intervention.